The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1186/s12888-022-04133-5
|View full text |Cite
|
Sign up to set email alerts
|

A mirror-image analysis of psychiatric hospitalisations among people with severe mental illness using Independent Supported Housing

Abstract: Background Evidence on the effectiveness of Independent Supported Housing (ISH) for non-homeless people with severe mental illness primarily comes from observational cohort studies, which have high risk of bias due to confounding by time-invariant sample characteristics. The present study proposes an alternative study design known from pharmacology to overcome this bias and strengthen evidence. Methods We conducted a retrospective mirror-image anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition to the OS design, other quantitative study designs should be explored to complement existing evidence. For example, the self-controlled mirror-image design known from pharmacology has been shown to overcome the risk of confounding owing to time-invariant sample characteristics because every subject acts as its own control ( 60 , 61 ). This design allows for causal inference when time-variant confounding (i.e., regression toward the mean) is adequately addressed ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the OS design, other quantitative study designs should be explored to complement existing evidence. For example, the self-controlled mirror-image design known from pharmacology has been shown to overcome the risk of confounding owing to time-invariant sample characteristics because every subject acts as its own control ( 60 , 61 ). This design allows for causal inference when time-variant confounding (i.e., regression toward the mean) is adequately addressed ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the existing research literature, these instruments have been shown to reduce coercive admissions (de Jong et al, 2016). Residential support services have also been shown to have a preventive effect on admission to psychiatric hospitals (Adamus et al, 2022a, Adamus et al, 2022b. A consistent expansion of outpatient support services, even outside of crisis situations, could make a significant contribution to reducing inpatient stays.…”
Section: Dilemmas Of a Consistent Human Rights Implementation In Psyc...mentioning
confidence: 99%
“…In addition, they generally include representative samples, testing objective outcome variables, such as the number of hospital admissions or emergency department visits. 19 , 21 , 22 However, evidence from mirror-image studies investigating LAIs in BD is scattered and has not been systematically evaluated so far. This would be helpful to clarify the possible role of LAIs for the maintenance treatment of BD from the relevant body of evidence accumulated in the last few years.…”
Section: Introductionmentioning
confidence: 99%